LINGUISTIC AND LINGUACULTURAL ASPECTS OF CHILDREN'S ANECDOTES IN UZBEK AND ENGLISH LANGUAGES (International journal of artificial intelligence, 2026)
This article presents a comparative analysis of the linguistic and linguacultural aspects of children’s anecdotes in the Uzbek and English languages. Children’s anecdotes, as a distinct genre of oral discourse, reflect children’s cognitive processes, communicative strategies, and the transmission of cultural values through language. The main aim of the study is to identify both universal and culture-specific features found in children’s anecdotes across different linguistic and cultural contexts.The research adopts a qualitative approach and is based on a corpus of children’s anecdotal texts in Uzbek and English. The analysis employs lexical, syntactic, stylistic, pragmatic, and linguacultural frameworks. Lexical analysis focuses on everyday vocabulary and humor-generating mechanisms, while syntactic analysis examines sentence structure and dialogic patterns. Stylistic and pragmatic approaches are applied to identify expressive means and communicative intentions, and linguacultural analysis reveals the reflection of national mentality and social values in humorous discourse.The results demonstrate that children’s anecdotes in both languages share universal characteristics such as simplicity, cognitive accessibility, and humor based on logical incongruity. At the same time, significant linguacultural differences are observed. English children’s anecdotes tend to rely on wordplay, irony, and individualistic expression, whereas Uzbek anecdotes are more often based on situational humor, literal interpretation, and culturally familiar contexts that emphasize collective and moral values.The study highlights the close interaction between language and culture in children’s discourse and contributes to the fields of comparative linguistics, folklore studies, and intercultural communication.